Analisis Data Menggunakan Tools Tableau Untuk Visualisasi Data Peserta Tkk Pada Dashboard Bina Konstruksi - Aji Ali Nugraha; Abdul Rahim; Arda Fahmi Achmad; Awang Herjunie Nurdy; Eka Agung Prayoga; Muhammad Azriel Yahya (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In today's digital era, data is one of the most important things in decision making. However, too much and complex data can be difficult to understand. Therefore, tools are needed to help in visualizing data efficiently and effectively.Â This study aims to explore how the Tableau tool can be used to visualize TKK participant data on the Bina Konstruksi dashboard. This research uses quantitative methods with data analysis using Tableau tools.Â The results showed that data analysis with the Tableau tool can be used to visualize TKK participant data on the Bina Konstruksi dashboard. The resulting data visualization provides more comprehensive information so that it is easier for users to understand.Â Based on the results of this study, it can be concluded that the Tableau tool can be a solution to improve the effectiveness and efficiency of TKK participant data visualization on the Bina Konstruksi dashboard. This can provide benefits for TKK participants, TKK training organizers, and Bina Konstruksi dashboard users.